A Phase I Study of Dinaciclib in Combination With MK‐2206 in Patients With Advanced Pancreatic Cancer. Issue 6 (1st August 2020) - Murphy, Adrian G.; Zahurak, Marianna; Shah, Mirat; Weekes, Colin D.; Hansen, Aaron; Siu, Lillian L.; Spreafico, Anna; LoConte, Noelle; Anders, Nicole M.; Miles, Tearra; Rudek, Michelle A.; Doyle, L. Austin; et al.
Abstract : The combination of drugs targeting Ral and PI3K/AKT signaling has antitumor efficacy in preclinical models of pancreatic cancer. We combined dinaciclib (small molecule cyclin dependent kinase inhibitor with MK‐2206 (Akt inhibitor) in patients with previously treated/metastatic pancreatic cancer. Patients were treated with dinaciclib (6–12 mg/m 2 i.v.) and MK‐2206 (60–135 mg p.o.) weekly. Tumor biopsies were performed to measure pAKT, pERK, and Ki67 at baseline and after one completed cycle (dose level 2 and beyond). Thirty‐nine patients participated in the study. The maximum tolerated doses were dinaciclib 9 mg/m 2 and MK‐2206 135 mg. Treatment‐related grade 3 and 4 toxicities included neutropenia, lymphopenia, anemia, hyperglycemia, hyponatremia, and leukopenia. No objectives responses were observed. Four patients (10%) had stable disease as their best response. At the recommended dose, median survival was 2.2 months. Survival rates at 6 and 12 months were 11% and 5%, respectively. There was a nonsignificant reduction in pAKT composite scores between pretreatment and post‐treatment biopsies (mean 0.76 vs. 0.63; P  = 0.635). The combination of dinaciclib and MK‐2206 was a safe regimen in patients with metastatic pancreatic cancer, although without clinical benefit, possibly due to not attaining biologically effective doses. Given the strong preclinical evidence of Ral and AKT inhibition, further studies with better tolerated agents should be considered.